Society Participation in Course and Training Institutions (LKP) Bougenville Kecamatan Lubuk Basung - Audina Melinda; MHD. Natsir (Universitas Negeri Padang, 2023)
This study aims to explain: (1) community participation in terms of education on the development of LKP Bougenville Lubuk Basung in the form of financial participation, academic participation, cultural participation and evaluative participation (2) The level of community participation in education. This study uses a qualitative approach with a case study method based on Creswell's theory. The research setting was carried out at LKP Bougenville which is located on Jl. Gajah Mada Hilir Pasar, Lubuk Basung, Agam District, West Sumatra Province . Sources of data in this research are managers, instructors, LKP Bougenville employees, community, community leaders and alumni of course participants. Data collection techniques in this study were observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. In this study, the data validity technique used source triangulation and technical triangulation. The results of this study indicate that: (1) community participation in terms of education on the development of LKP Bougenville Lubuk Basung has been carried out well. This can be seen from several aspects, such as participation in financial activities in the form of funding for educational activities for courses required by LKP Bougenville. Academic participation in the form of the role of parents in encouraging and motivating and facilitating their children during the education process. Cultural community participation in the form of voluntary promotion of the success of the program at LKP Bougenville. Evaluative participation in the form of community involvement in controlling the implementation of education, so that the community can provide feedback and assessments of the performance of educational institutions. (2) The implementation of the level of community participation in education at LKP Bougenville is at a strong level at the Partnership level.